Utility of Prostate-Specific Antigen Isoforms and Prostate Health Index in the Diagnosis of Metastatic Prostate Cancer - Raju, Govinda Nanjaiah Laxmana; Bhat, Parineetha P.; Nagini, Siddavaram (Journal of Laboratory Physicians, 2022)
Objective The current study was undertaken to investigate the utility of total prostate-specific antigen (tPSA), its isoform [-2] proPSA (p2PSA), and prostate health index (PHI) in the diagnosis of metastatic prostate cancer (PCa).Materials and Methods This study was conducted from March 2016 to May 2019. Eighty-five subjects who were diagnosed with PCa for the first time, following transrectal ultrasound-guided prostate biopsy, were included in the study. The prebiopsy blood samples were analyzed in Beckman Coulter Access-2 Immunoanalyzer for tPSA, p2PSA, and free PSA (fPSA), and the calculated parameters included %p2PSA, %fPSA, and PHI. Mann–Whitney's U test was used as test of significance, and p-value less than 0.05 was considered statistically significant.Results Of the 85 participants, 81.2% (n = 69) had evidence of metastasis, both clinically and pathologically. The median tPSA (ng/mL), p2PSA (pg/mL), %p2PSA, and PHI were significantly higher in the group with evidence of metastasis (46.5 vs. 13.76; 198.0 vs. 35.72; 3.25 vs. 1.51; 237.58 vs. 59.74, respectively). The sensitivity (%), specificity (%), negative predictive value (%), and positive predictive value (%) to diagnose metastatic PCa of tPSA at a cutoff of 20 ng/mL, PHI at a cutoff of 55, and %p2PSA at a cutoff of 1.66 were 92.7, 98.5, and 94.2; 37.5, 43.7, and 62.5; 54.5, 87.5, and 71.4; and 86.4, 88.3, and 91.5, respectively.Conclusion Using tests such as %p2PSA and PHI in the standard armamentarium for the diagnosis of metastatic PCa in addition to PSA will help in selecting the appropriate treatment strategy, including active surveillance.
Keywords: prostate cancer; prostate health index; prostate-specific antigen; PSA isoforms